New experimental correlations to predict water-oil relative permeability curves affected from asphaltene deposition - Khanifar, A. (Offshore Technology Conference, 2014)
Asphaltene precipitation and deposition may occur during natural depletion, displacement of reservoir oil by C02, hydrocarbon gas or WAG application. They can affect reservoir performance and cause formation damage such as porosity and permeability reduction, wettability alteration and relative permeability changes. Moreover, asphaltene deposition may lead to plugging of wellbore and production surface facilities. The dynamic displacement efficiency in porous media is controlled by relative permeability, and asphaltene deposition can alter the original characteristics ofthe relative permeability. To the best of our knowledge, there exists no correlation available in the literature that can be used to predict the relative permeability alteration due to asphaltene deposition which considers the amount of asphaltene as an independent variable. Although the exact physics on how this alteration occurs is still a research topic, it has been reported that some of its effect may be captured by wettability change and relative permeability shift from a water-wet to an oil-wet (or a mixed-wet) system In this paper, new experimental correlations are presented to predict the effect of asphaltene deposition on irreducible water saturation, residual oil saturation and relative permeability for water-oil systems. The correlations are obtained by history matching experimental data from several dynamic displacement experiments (conducted on different core-plug samples, but having the same rock properties under reservoir conditions) with the corresponding data from a two-phase one-dimension black-oil simulation model. Copyright 2014, Offshore Technology Conference.